External factors affecting investment decisions of companies - Piotr Bialowolski; Dorota Weziak-Bialowolska (Economics: The Open-Access, Open-Assessment E-Journal, 2014)
In this paper, we attempt to investigate the importance of certain external factors on the investment decisions made by Polish companies. With the use of data from the tailor-made Survey on Receivables, we (1) examine factors influencing investment decisions of companies in Poland; (2) assess the relation between branch, company size and investment factors; (3) evaluate the importance of the investment factors; and (4) determine the relative influence of these factors on the company-level investment reductions. The results show that first, although the problem of payment delays is the most important single issue determining the investment decisions of Polish companies, its importance decreases when analysed simultaneously with other issues. Second, among the indicators selected for an assessment of investment decisions, two driving forces determine the investment decisions of Polish companies - namely, macroeconomic factors and law-related factors, with the relative importance of the former lower than the latter. Third, there is a positive association between the importance of each of the two factors and the actual investment reductions, implying that among companies facing higher investment reductions, the importance of macroeconomic and law-related factors is higher.
Keywords: D92; G11; G31; 330; investment decisions; company; survey; structural equation modelling